The Implementation of Financial Accounting Standards (PSAK) 109, Accounting Information Systems, Internal Control, and Employee Performance on the Quality of Financial Reports at BAZNAS Garut District - Burhanudin, Ujang; Farid, Diana; Solihin, Dadin (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The problem raised in this study, namely regarding the quality of the financial statements of BAZNAS Garut Regency during the five years from 2016 to 2021, related to it has not fully met qualitative characteristics, such as relevant, reliable, easy to understand, and compatible. This causes the assessment of reasonable opinions without exception to be inconsistent, which the authors consider to be an important new aspect of research. This study aims to analyze the influence of the implementation of PSAK 109 (X1), accounting information system (X2), internal control (X3), and employee performance (X4) on the quality of financial statements (Y), both partially and simultaneously. The results of the study show that each variable, namely the implementation of PSAK 109 (X1), accounting information system (X2), internal control (X3), and employee performance (X4), partially has a significant influence on the quality of financial statements. Simultaneously, these variables had a significant influence of 93.9% on the quality of financial statements, while 6.1% were influenced by other factors that were not tested in this study.